An Analysis of Demand-based Factors for Broadband Migration - Satitsamitpong, Manit; Otsuka, Tokio; Jitsuzumi, Toshiya; Mitomo, Hitoshi (Asian Journal of Applied Economics, 2013)
Abstract This paper explores the factors that influence the users’ decision to migrate from narrowband to broadband services. Data used were obtained from web questionnaire surveys in Japan and the annual Internet User Profile Survey of the National Electronics and Computer Technology Center (NECTEC) in Thailand. The economic, technological and demographic factors were analyzed by using a mixed logit model. The results suggest that price, as a proxy for economic factor, is an important factor in a developing country. In Thai case, lowering the price of broadband services to 50% would increase the probability of the users migrating to broadband by more than 5%. Demographic factors including income, location, and internet experience also contribute to the decision, but their impacts are smaller than that of price. Contrary to previous studies, speed is not a statistically significant factor. Keywords : broadband, choice probability, mixed logit model, discrete choice modelJEL Classification : C25, D12, L63